Effects of Human Disturbance and Human-made Barriers on the Behaviour, Physiology, and Genetic Structure of Painted Turtle Populations - Turcotte, Audrey (Université d'Ottawa / University of Ottawa, 2023)
Human activities, such as urban expansion, have led to an increase in contacts between humans and wildlife and have resulted in the loss and isolation of suitable habitats for animal populations. These human-induced pressures threaten the persistence of animal populations and understanding how animals respond to them is crucial for conservation. A multidisciplinary approach that includes different biological components of a species, such as behaviour, physiology, and population genetic structure, is necessary to obtain a comprehensive insight into the impact of human activities on wildlife. Turtle populations are particularly vulnerable to human disturbance due to their life-histories, but there is limited information available on how human-induced perturbations affect different components of their biology. In this context, my thesis aims to evaluate the impact of human disturbance and human-made barriers on the behaviour, physiology, and genetic structure of painted turtles (Chrysemys picta) in the Rideau Canal, Ontario, Canada. In chapter one, I evaluate the relationship between risk-taking behaviours and human disturbance levels. In chapter two, I assess the impact of human disturbance on the relationships between risk-taking behaviours, physiological response, and colouration. Finally, in chapter three I characterize the genetic structure of painted turtles in the Rideau Canal and assess the impact of human-made barriers, such as locks, on the genetic substructuring occurring in the system. Overall, I show that human activities and human-made barriers have several impacts on painted turtle biology, from influencing their risk-taking behaviours to inducing physiological changes and causing genetic discontinuities among groups. More specifically, in chapter one, I show that painted turtles are consistent in their risk-taking behaviour and that turtles located in areas with more boat activities are more prone to take risks, suggesting that being risk-prone may be associated with a greater tolerance to human disturbance. I also show that painted turtles exhibit a lower physiological response when human activity is limited, indicating that human activities may induce physiological costs on wildlife. In addition, I report variations in physiological responsiveness according to the propensity of turtles to take risks, where risk-prone males have higher physiological responses than risk-averse males, highlighting the importance to use different disciplines to better understand the consequences of human activities and how the different biological components interact together under human-induced pressures. Finally, I found genetic substructuring among groups of turtles within the Rideau Canal, which seems to be partly caused by locks, especially when they are numerous and clustered in space. My results provide a better understanding of the impact of human disturbance on animal populations as well as information that could be used to better guide management decisions that are relevant to species vulnerable to human activities, such as turtles. Monitoring animal behaviour alongside physiological biomarkers and genetic populational trends can aid in the development of better adapted conservation strategies.
Keywords: Painted turtles